2018
DOI: 10.1093/jn/nxy157
|View full text |Cite
|
Sign up to set email alerts
|

WIC and non-WIC Infants and Children Differ in Usage of Some WIC-Provided Foods

Abstract: BackgroundUSDA's Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) provides expert-chosen supplemental foods to improve the diets and health of low-income infants and children <5 y of age, but dietary behaviors of WIC participants are not well characterized.ObjectiveThe purpose of this analysis was to examine differences in food consumption patterns between WIC participants and nonparticipants.MethodsFITS 2016 is a nationwide cross-sectional study of children <4 y (n = 3235). Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…However, the prevalence and duration of exclusive breastfeeding still fell short of the Healthy People 2020 goals. Guthrie et al ( 13 ) found that infants participating in WIC were less likely to be put to the breast at all, and if they were, were breastfed for a shorter time than non-WIC participants.…”
Section: Key Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the prevalence and duration of exclusive breastfeeding still fell short of the Healthy People 2020 goals. Guthrie et al ( 13 ) found that infants participating in WIC were less likely to be put to the breast at all, and if they were, were breastfed for a shorter time than non-WIC participants.…”
Section: Key Findingsmentioning
confidence: 99%
“…The prevalence of introducing solids <4 mo of age continued to decline ( 10 ), compared with FITS 2008 ( 11 ), confirming NHANES data that also suggest a lower prevalence of complementary feeding in very young infants than previously reported ( 8 ). However, infants consuming any formula were more likely to be introduced to complementary foods <4 mo of age ( 10 ), whereas, paradoxically, infants participating in WIC (who are more likely to be fed formula) were less likely to be introduced to complementary foods <4 mo of age ( 13 ). This suggests that WIC recipients are influenced by what foods WIC provides (i.e., for very young infants, WIC provides formula, but not complementary foods).…”
Section: Key Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…The new WIC program regulations included steps such as eliminating fruit juice from the infant package, additional promotion of breastfeeding initiation and duration, and routine switch to low- or nonfat milk for older children. All of this is summarized in detail in the paper by Guthrie et al ( 39 ) for foods and that by Jun et al ( 40 ) for nutrients. These findings demonstrate opportunities for improvements in dietary intake in WIC participants and to improve the WIC system of nutrition education and supplement foods.…”
Section: Highlights Of Fits 2016mentioning
confidence: 99%